Intensive method of assessment and classification of the bone marrow iron status: A study of 80 patients - Rajeshwari S Bableshwar; Maitrayee Roy; Akshay Bali; Prakash V Patil; Suvarna Inumella (Wolters Kluwer Medknow Publications, 2013)
Background: The increasing prevalence of multiple co-morbidities among anemic patients with chronic diseases have made the use of serum ferritin (which is also an acute phase reactant) and transferrin saturation more challenging in diagnosing iron deficiency. Microscopic examination of bone marrow aspirate is the gold standard" for assessing marrow iron store. However, conventional Gale's method assesses iron in marrow fragments alone which provides little valuable information about functional iron deficiency seen in many chronic diseases. Aim: To perform an intensive bone marrow iron grading by assessing iron in fragments, in macrophages around fragments and in erythroblasts and to correlate the marrow iron store results with serum ferritin. Materials and Methods: A descriptive study of Perl's Prussian blue stained bone marrow aspirate smears of 80 adult patients with moderate to severe anemia. Bone marrow iron was assessed by both the Gale's method and the intensive method and correlated with serum ferritin. Results: The intensive grading system revealed normal iron stores in 37.5% cases, depleted iron stores in 16.25% patients while 23.75% and 22.5% patients had functional iron deficiency and combined deficiency, respectively. Mean log ferritin concentration was significantly lower in patients with depleted iron stores (0.91 μg/l) in comparison to those with normal iron stores (2.13 μg/l; P = 0.001), functional iron deficiency (2.65 μg/l; P = 0.000), or combined deficiency (2.04 μg/l; P = 0.002). Conclusion: Intense marrow iron examination provides a useful iron status classification which is of particular importance in cases of chronic diseases and inflammation.